Gaps in pre and post-operational tasks for open distance learning (ODL) implementation - Ahmad, Siti Arpah; Zainol, Zarina (Penerbit UiTM (UiTM Press), 2026)
This work aims to review the operational tasks involved in implementing Open Distance Learning (ODL). Since the outbreak of Covid-19, ODL has become popular, especially for postgraduate programs. The scope is to review the pre- and post-tasks studied in prior work on ODL implementation. Examples of pre-tasks include applications for accreditation, and post-tasks are students’ performance in adopting the ODL approach. A systematic review methodology was used based on 15 articles retrieved from Google Scholar. The string used to perform the literature search is (“Open Distance learning” AND “postgraduate program” OR “computing” OR “Self-Instructional Material” OR “accreditation”). Results show that most prior work focused on post-tasks, such as students’ performance and the effectiveness of Self Instructional Material (SIM). At the same time, a few studies report on the pre-task hurdles of applying accreditation.